2004
DOI: 10.2334/josnusd.46.149
|View full text |Cite
|
Sign up to set email alerts
|

Intra-familial distribution of nine putative periodontopathogens in dental plaque samples analyzed by PCR

Abstract: It is of great importance to understand the distribution of periodontopathogens within family members when considering the risk of periodontitis in children. The purpose of this study was to investigate the distribution of periodontopathogens among family members. We used the polymerase chain reaction method to test 4,8, and 7 probands with healthy gingiva, gingivitis, and periodontitis, respectively, and their 60 immediate family members. Plaque samples were collected from all erupted teeth sites using a ster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 23 publications
(25 reference statements)
1
22
0
Order By: Relevance
“…While the data are rather sparse, similar types of outcomes can be inferred from the existing literature in humans, where there exists a familial tendency for the expression of periodontitis, particularly that related to aggressive periodontitis and infection with A. actinomycetemcomitans (58). Analogous findings have also supported an increased prevalence of periodontitis in families of parents with severe disease, which is generally related to high levels of specific pathogens at the disease sites (45,59,60), although negligible information is available regarding the dynamics of the transmission of specific bacteria from infected parents to their offspring.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…While the data are rather sparse, similar types of outcomes can be inferred from the existing literature in humans, where there exists a familial tendency for the expression of periodontitis, particularly that related to aggressive periodontitis and infection with A. actinomycetemcomitans (58). Analogous findings have also supported an increased prevalence of periodontitis in families of parents with severe disease, which is generally related to high levels of specific pathogens at the disease sites (45,59,60), although negligible information is available regarding the dynamics of the transmission of specific bacteria from infected parents to their offspring.…”
Section: Discussionsupporting
confidence: 57%
“…Nevertheless, the detailed characteristics of this microbial acquisition remain speculative, and minimal information is available regarding the development of host responses to this oral colonization in young individuals. It does appear that these bacteria that are acquired early in life become integrated into the commensal autochthonous oral microbial ecology within the individual (43)(44)(45)(46).…”
mentioning
confidence: 99%
“…These results for adult periodontitis patients were similar to the present results obtained in children. We also reported previously that the prevalence of P. gingivalis was 71.4% in both fathers and mothers of proband families, while it was 35.7% in their children (24), and we found that parents are an important source of periodontal pathogens that colonize the oral cavities of their children (24). On the other hand, P. gingivalis was shown to be less easily transmitted from parents to children (25), while another study noted that the pathogen may be difficult to transmit or require a longer period of time for colonization (26).…”
Section: Discussionmentioning
confidence: 98%
“…It is clear that levels of gram-negative periodontal pathogens increase with age, although studies of young humans and nonhuman primates demonstrate that many microorganisms associated with periodontal pathogenesis are acquired early in life and become integrated into the commensal autochthonous oral microbial ecology (9,29,30,56). However, it remains unclear how the age of the host impacts recognition of and response to these oral microorganisms.…”
mentioning
confidence: 94%